The sufferings and self care of hospitalized elderly - ethnography study - Tuoto, Fernada Spiel; Lenardt, Maria Helena; Venturi, Kriscie Kriscianne (Online Brazilian Journal of Nursing, 2009)
Elderly oncological patients are marked by several limitatons and impositions generated by the disease and aging process, which lead them to hospitalization. This is a qualitative research with an ethnographic approach. This study took place at a clinical ward in a reference hospital for cancer treatment, in the city of Curitiba, Paraná. This study aimed to interpret hospitalized elderly cancer patients suffering and the self care performed to minimize their suffering. The data was collected in 2007, from April to June, by participant observation and ethnographic interview. The following methodological phases were considered to analyze the data: domain, taxonomic and thematic. As a result of the research, four cultural domains emerged as well as a cultural theme titled: “through the elderly calvary of pain, the belief that sustains life”. Intense physical pain, lack of appetite, breathing difficulty and impossibility of walking and working are noticed by the elderly as the main suffering related to cancer. It is concluded that informers make direct allusion to a calvary in which religion was used as the most essential self care.